Bread art e-book - Šumer, Anita (knjige, 2021)
Unique ebook on bread art with 5 techniques; stenciling, paiting, topping, scoring, beautifying with dough ornaments, dried flowers.With 20 in-detail tutorials.5 ways to giftwrap bread.
Keywords: Krašenje; Kruh; Peka